Metapenta: visualización y análisis de redes metabólicas (2021)
Various approaches have been proposed to deal with the problem of modeling, simulating, and representing metabolic networks, which can be summarized in three main models: continuous, discrete, and hybrid. In this work, it was proposed to model metabolic networks with Petri nets. A Petri net represents discrete events in the form of a graph that fulfills properties of distribution, concurrency, and parallelism. For this problem, MetaPenta was implemented. MetaPenta is a tool that can perform different queries on metabolic networks, for example, finding the minimum path between two metabolites, identifying metabolites as sinks and sources, visualizing the metabolic network as a Petri net, among other functionalities. The implemented tool was compared with other software developments such as the Costas Maranas Research group's scripts and Fluxer tool. It was found that for the gap find's problem, the software's outputs were very similar, even though the approaches to find these metabolites were very different. On the other hand, in terms of performing, Fluxer can render several types of charts. However, in most cases, these representations omit much of the information (for example, the reaction enzymes), while the Petri net representation implemented in MetaPenta does not. In the future, it is expected to increase the functionalities of MetaPenta to handle the reversibility of reactions and facilitate the automatic reconstruction of metabolic networks.